2021
DOI: 10.1016/j.jeconom.2020.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the fraction of unreported infections in epidemics with a known epicenter: An application to COVID-19

Abstract: We develop an analytically tractable method to estimate the fraction of unreported infections in epidemics with a known epicenter and estimate the number of unreported COVID-19 infections in the US during the first half of March 2020. Our method utilizes the covariation in initial reported infections across US regions and the number of travelers to these regions from the epicenter, along with the results of an early randomized testing study in Iceland. Using our estimates of the number of unreported infections… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…To account for underreported air travel cases, the number of unreported COVID-19 cases in the general global population is assumed to apply. Recent estimates indicate global under-reporting to be a 10-fold [ 6 , 7 ], 23-fold ]8[ and 54-fold [ 9 ] multiplier of the current reported cases.…”
Section: Methodsmentioning
confidence: 99%
“…To account for underreported air travel cases, the number of unreported COVID-19 cases in the general global population is assumed to apply. Recent estimates indicate global under-reporting to be a 10-fold [ 6 , 7 ], 23-fold ]8[ and 54-fold [ 9 ] multiplier of the current reported cases.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, reported cases represent a subset of the total number of infected cases, as sometimes only the most severe cases of symptoms are reported. On the basis of Liu et al (2020) [ 6 , 10 ], our approach is based on the knowledge of the data of new reported cases (typically weekly) over the time course of the pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, we cannot convert our cumulative reported exponential function to the least-square log transformation, since we have an error that we need to estimate. In previous studies, an a priori constant has to be chosen, and not estimated, for [ 10 ]; then, a fitted least-square log transformation was applied to the cumulative data. In this paper, we estimate the parameters directly using the self-starting functions proposed [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent work attempts to estimate the level of under-reporting in the USA during the first half of March 2020 using travel data from epicentres. 2 Another study 3 uses a Bayesian analysis to get an estimate of the cumulative number of unreported cases in the USAS up to 18 April 2020.…”
Section: Introductionmentioning
confidence: 99%